Teaching UML Models with FLOSS Projects: A Study Carried out during the Period of Social Isolation Imposed by the COVID-19 Pandemic - Silva, Fernanda Gomes; Lessa, Moara Sousa Brito; Lopes, Nádia da Luz; Chavez, Christina von Flach G. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2020)
Software Engineering Education must include professional practice experiences so that students are able to specify, design, implement, maintain and evaluate computer systems, using appropriate theories, practices and tools. However, teaching Software Engineering (SE) principles, concepts and practices and relating them to real-world scenarios are challenging tasks. The adoption of Free/Libre/Open-Source Software (FLOSS) projects can assist in facing these challenges. This paper presents an experience report on the pedagogical use of FLOSS projects in a SE course, in the context of social isolation imposed by the COVID-19 pandemic. The course was fully virtualized, with supporting tools such as Google Classroom, Google Meet, Github, Padlet and Trello, and modeled after an instructional design based on Bloom's taxonomy of cognitive learning objectives. FLOSS projects were used in the context of software modeling activities with UML class, sequence and activity diagrams. An online survey with twenty-six (26) students and an interview with the instructor were conducted to collect their perceptions about such experience. Results showed that most students (i) agreed that the instructional methods addressed the knowledge, comprehension and application levels in a satisfactory way; (ii) were satisfied in working with real software projects developed by others; and (iii) liked the developed activities and the tools used in the classes. The instructor and students (iv) missed face-to-face activities; and (v) agreed that the instructional design could be used in future face-to-face SE classes.